Reversible inhibition of urea exchange in rat hepatocytes. - R M Effros; E Jacobs; A Hacker; K Ozker; C Murphy (The Journal of Clinical Investigation, 1993)
Urea exchange is enhanced in renal collecting duct cells and erythrocytes by transporters which can be inhibited by phloretin and urea analogs such as thiourea. In this study, evidence for a comparable transporter was found in rat livers perfused with solutions which contained no red cells and in suspensions of hepatocytes. Bolus injections containing 125I-albumin (intravascular indicator), 99mTc-DTPA (extracellular indicator), 3HOH (water indicator), and [14C]urea were administered into the portal vein and fluid was collected from the hepatic vein. Under control conditions, [14C]urea and 3HOH emerged from the hepatic vein at nearly the same rate. However when the perfusate contained 2.5 mM phloretin (equivalent to 0.058 mM phloretin not bound to albumin), the amount of [14C]urea which had been recovered in the hepatic venous outflow by the time of peak 125I-albumin concentrations exceeded 3HOH recovery by a factor of 2.31 +/- 0.23 (n = 7). When the perfusate contained 200 mM thiourea, the comparable recovery of [14C]urea from the hepatic veins exceeded that of 3HOH by a factor of 3.48 +/- 0.44 (n = 7). These effects were at least partially reversible and suggested inhibition of urea transporters in hepatocytes. This conclusion was supported by studies of unloading of [14C]urea from hepatocytes which were exposed to unlabeled solutions: in the presence of phloretin, the amount of [14C]urea remaining within hepatocytes at 4 s was approximately twice that remaining in hepatocytes which had not been exposed to phloretin. Rapid transport of urea out of hepatocytes may increase urea synthesis and minimize cellular swelling due to urea accumulation.